Diatoms as a tracer of hydrological connectivity: are they supply limited?. Issue 4 (17th September 2015) - Coles, Anna E.; Wetzel, Carlos E.; Martínez‐Carreras, Núria; Ector, Luc; McDonnell, Jeffrey J.; Frentress, Jay; Klaus, Julian; Hoffmann, Lucien; Pfister, Laurent
Abstract: Recent work has shown that aerial diatoms are a useful ecological tracer of hydrological connectivity in the hillslope–riparian zone–stream (HRS) system. While such work has improved both our understanding of catchment functioning and aerial diatom taxonomy, assemblages and distribution, further work is hampered by lack of data on diatom population depletion during rainfall events. We still do not know whether or not diatom tracers are supply limited. Here we test the null hypothesis that aerial diatoms exhibit infinite supply in the context of natural rainfall events. Rainfall simulation experiments were conducted in a small forested catchment in northwest Luxembourg. We extracted periodically soil surface samples and overland flow samples for diatom population size and species assemblage analyses. Diatom population size was quantified using a new approach we have developed, which involves extracting diatoms using carbonated water and an isopycnic separation technique. Our results showed that pre‐event population size was c . 96 100 diatoms per cm 2 in the riparian zone. During the artificial rainfall event, the diatom population was depleted by 72% to 27 200 diatoms per cm 2 . The diatom assemblage was characteristic of a frequently disturbed environment. Overall, these results suggest that diatoms are supply limited, and are flushed significantly throughout rainfall events. Nevertheless, based on the data from these 1 in 10‐year rainstorm simulations, the riparian zone diatom population is unlikely to be exhausted on an event time scale. Further research is now underway to investigate the spatial and temporal variability of aerial diatom communities across a range of storm sizes. Copyright © 2015 John Wiley & Sons, Ltd.